Forensic parameters and admixture in seven geographical regions of the Guerrero state (South, Mexico) based on STRs of the Globalfiler® kit - José Alonso Aguilar-Velázquez; Gorge Locia-Aguilar; Briselda López-Saucedo; Sandra Deheza-Bautista; Alma Faviola Favela-Mendoza; Héctor Rangel-Villalobos (Annals of Human Biology, 2018)
Background: New commercial STR kits have emerged with greater numbers of markers, which allows for obtaining stronger conclusions in forensic casework, which has been poorly studied in Mexico. Aim: To obtain forensic parameters and to analyse the genetic relationships, structure and admixture in seven geographic regions of Guerrero state (South, Mexico) based on the Globalfiler® kit. Subjects and methods: A total of 245 unrelated Mexican individuals from seven regions of the state of Guerrero were analysed with the Globalfiler® kit. Forensic parameters, pairwise comparisons, genetic distances, structure analysis and admixture levels were estimated. Results: Allele frequencies and forensic parameters of 22 STRs were estimated in this Mexican population sample. The combined power of exclusion and power of discrimination values were > 99.9999% and >99.99999999%, respectively. The Native American, European and African ancestries estimated in the Guerrero state population were 70.9%, 25.9% and 3.2%, respectively. Conclusion: Forensic validation of the Globalfiler® kit was performed in the Guerrero state population. The geographic isolation level seems to be the principal factor in defining genetic relationships and admixture among the Guerrero sub-populations. Despite the intrinsic limitations of STRs for admixture analysis, these results are very close to previous values based on AIMs and genome-wide SNPs.